Cardiovascular Event Reduction and Adverse Events Among Subjects Attaining Low-Density Lipoprotein Cholesterol <50 mg/dl With Rosuvastatin: The JUPITER Trial (Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin) - HSIA, Judith; MACFADYEN, Jean G; MONYAK, John; RIDKER, Paul M (Journal of the American College of Cardiology, 2011)
The purpose of this study was to assess the impact on cardiovascular and adverse events of attaining low-density lipoprotein cholesterol (LDL-C) levels <50 mg/dl with rosuvastatin in apparently healthy adults in the JUPITER (Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin) trial. The safety and magnitude of cardiovascular risk reduction conferred by treatment to LDL-C levels below current recommended targets remain uncertain. A cohort of 17,802 apparently healthy men and women with high-sensitivity C-reactive protein ≥2 mg/l and LDL-C <130 mg/dl were randomly allocated to rosuvastatin 20 mg daily or placebo, and followed up for all-cause mortality, major cardiovascular events, and adverse events. In a post-hoc analysis, participants allocated to rosuvastatin were categorized as to whether or not they had a follow-up LDL-C level <50 mg/dl. During a median follow-up of 2 years (range up to 5 years), rates of the primary trial endpoint were 1.18, 0.86, and 0.44 per 100 person-years in the placebo group (n = 8,150) and rosuvastatin groups without LDL-C <50 mg/dl (n = 4,000) or with LDL-C <50 mg/dl (n = 4,154), respectively (fully-adjusted hazard ratio: 0.76; 95% confidence interval: 0.57 to 1.00 for subjects with no LDL-C <50 mg/dl vs. placebo and 0.35, 95% confidence interval: 0.25 to 0.49 for subjects attaining LDL-C <50 mg/dl; p for trend <0.0001). For all-cause mortality, corresponding event rates were 0.67, 0.65, and 0.39 (p for trend = 0.004). Rates of myalgia, muscle weakness, neuropsychiatric conditions, cancer, and diabetes mellitus were not significantly different among rosuvastatin-allocated participants with and without LDL-C <50 mg/dl. Among adults with LDL-C <130 mg/dl and high-sensitivity C-reactive protein ≥2 mg/l, rosuvastatin-allocated participants attaining LDL-C <50 mg/dl had a lower risk of cardiovascular events without a systematic increase in reported adverse events.